2023
DOI: 10.1523/jneurosci.1677-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Selectivity Coding of Content-Temporal Detail by Dorsomedial Posterior Parietal Neurons

Lei Wang,
Xufeng Zhou,
Fu Zeng
et al.

Abstract: The dorsomedial posterior parietal cortex is part of a higher-cognition network implicated in elaborate processes underpinning memory formation, recollection, episodes reconstruction, and temporal information processing. Neural coding for complex episodic processing is however under-documented. Here we recorded extracellular neural activities from three male rhesus macaques (Macaca mulatta) and revealed a set of neural codes of ‘neuroethogram’ in the primate parietal cortex. Analyzing neural responses in macaq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Furthermore, they support the potential use of PPC oscillatory activity as a valuable tool for early detection and intervention in AD.episodic memory retrieval and updating, in uencing new memories based on current experiences [12][13][14]. Furthermore, functional magnetic resonance imaging (fMRI) studies have revealed a positive correlation between the strength of the functional connectivity between the PPC and the hippocampus, and spatial memory performance accuracy [15]. Speci cally, the dPPC connects with the anterior hippocampus in humans (equivalent to the ventral hippocampus in rodents), while the vPPC is linked to the posterior (dorsal in rodents) hippocampus.In this context, effective communication between the hippocampus and cortical regions, and modulation of these memory processes, rely on neural oscillations, particularly theta and gamma rhythms, and the degree of synchronization between these regions, known as inter-regional coherence [16][17][18].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, they support the potential use of PPC oscillatory activity as a valuable tool for early detection and intervention in AD.episodic memory retrieval and updating, in uencing new memories based on current experiences [12][13][14]. Furthermore, functional magnetic resonance imaging (fMRI) studies have revealed a positive correlation between the strength of the functional connectivity between the PPC and the hippocampus, and spatial memory performance accuracy [15]. Speci cally, the dPPC connects with the anterior hippocampus in humans (equivalent to the ventral hippocampus in rodents), while the vPPC is linked to the posterior (dorsal in rodents) hippocampus.In this context, effective communication between the hippocampus and cortical regions, and modulation of these memory processes, rely on neural oscillations, particularly theta and gamma rhythms, and the degree of synchronization between these regions, known as inter-regional coherence [16][17][18].…”
mentioning
confidence: 60%
“…episodic memory retrieval and updating, in uencing new memories based on current experiences [12][13][14]. Furthermore, functional magnetic resonance imaging (fMRI) studies have revealed a positive correlation between the strength of the functional connectivity between the PPC and the hippocampus, and spatial memory performance accuracy [15]. Speci cally, the dPPC connects with the anterior hippocampus in humans (equivalent to the ventral hippocampus in rodents), while the vPPC is linked to the posterior (dorsal in rodents) hippocampus.…”
mentioning
confidence: 99%